Diet and cancer (Swiss Medical Weekly, 2011)
Large claims have been made for the effectiveness of particular diets in preventing cancer or inhibiting its progression. However, more recent clinical studies have not confirmed this. Instead it seems that rather than specific dietary constituents, total calories influence cancer incidence and progression. In this review article, we summarise and interpret the available evidence for links between diet and cancer.